Informal housing in Cape Town : delivery, formalization and stakeholder viewpoints - Tredoux, Marius (Marius Jacobus) (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2009.